Designing tracers for PET imaging of the urokinase‐type plasminogen activator receptor from a cyclic uPA‐derived peptide: first in vitro evaluations. (6th June 2019) - Wacker, Anja; Bauder‐Wüst, Ulrike; Schäfer, Martin; Schmidt, Jana; Remde, Yvonne; Stadlbauer, Sven; Eder, Matthias; Liolios, Christos; Kopka, Klaus
Abstract : The treatment of cancer remains a major challenge, especially after tumour cell dissemination and metastases formation. Expression of the urokinase‐type plasminogen activation system including urokinase (uPA) and its receptor (uPAR) has been associated with the complex process of cell migration, a tumour's invasive potential as well as a reduced overall and disease‐free survival of patients with solid cancers and haematological disorders. A cyclic peptide cyclo [21, 29][d ‐Cys 21, Cys 29 ]‐uPA21‐30 was designed from the growth factor‐like domain (GFD) of urokinase whose binding to uPAR was found to inhibit tumour growth and spread of human ovarian cancer cells in mice. With the aim of visualising uPAR expression using PET imaging to attempt an estimate on the tumour's aggressiveness, the cyclic peptide was modified with an either C‐ or N‐terminally attached variable spacer and chelator. The free ligands were evaluated for their binding affinities to the isolated human uPAR and labelled with 68 Ga and 177 Lu to assess their lipophilicities and stabilities in human serum. Although retaining the full binding potential displayed by cyclo [21, 29][d ‐Cys 21, Cys 29 ]‐uPA21‐30 to its target was found to be a challenging task upon both C‐ and N‐terminal modification, chelator‐bearing ligands were identified that can serve as promising starting points in the development of uPAR‐addressing PET tracers. Abstract : The cyclic peptide cyclo [21, 29][d ‐Cys 21, Cys 29 ]‐uPA21‐30 was conjugated C‐ and N‐terminally with a variable linker and a chelator to design a uPAR‐targeting PET tracer. The free ligands were evaluated for their binding affinity to the isolated uPAR receptor and labelled with 68 Ga and 177 Lu to assess their log D 7.4 values and stabilities in human serum.